HOTS-Based Science Learning Outcomes Assessment Instrument for Measuring Elementary School Learning Outcomes - Arthadewi, Rara Indah; Bayu, I Gede Wira; Rati, Ni Wayan (Mimbar Ilmu, 2024)
Teachers should develop effective assessment instruments to measure student learning outcomes well. Assessment instruments must also improve students' thinking abilities (HOTS). However, teachers need help compiling assessment instruments based on Revised Bloom's KKO Taxonomy, and the assessment instruments prepared are still LOTS-oriented. So far, research has yet to discuss the preparation of HOTS-based science learning outcomes assessment instruments. Therefore, this research aims to develop a HOTS-oriented assessment instrument for science content. This research is development research with a 4-D model. The subjects of this research were 69 students and involved two expert lecturers/science experts. Data collection in this study used the multiple-choice test method. The data analysis techniques in this research are validity, reliability, distinguishability, level of difficulty, and quality of distractors. The results of the research show that the assessment instrument developed is declared valid, has high reliability (reliable), and the level of difficulty is in the very good category; in terms of different power, it is stated that the instrument has good different power, and the quality of the distractor functions well. The test results show that the HOTS-oriented science learning outcomes assessment instrument is suitable for measuring student learning outcomes. This research implies that continuously using the HOTS standard assessment instrument will improve students' thinking.